Skrjabin’s Magical Music: Just a Fantasy? - Molina Moreno, Francisco (Amaltea. Revista de Mitocrítica, 2018)
This article discusses the magical power attributed to music in the text of the Preparatory Act, by the Russian composer and pianist Aleksandr Skrjabin (1872-1915), and whether the contents of that text can be considered mythical or fantastic.